157k views
0 votes
PLEASE HELP. 15 POINTS

PLEASE HELP. 15 POINTS-example-1
User ZJorge
by
5.1k points

1 Answer

3 votes

Answer:

The first term is -5 and the common difference is 4

tn = -9+4n

Explanation:

Sn = 2n^2 -7n

The formula for the arithmetic sum is given by

Sn =n/2 (2a1 + d(n-1))

We set these equal

2n^2 -7n = n/2 (2a1 + d(n-1))

Factor out an n on the left side

n(2n-7) = n/2 (2a1 + d(n-1))

Divide each side by n

n/n(2n-7) = n/2*1/n (2a1 + d(n-1))

(2n-7) = 1/2 (2a1 + d(n-1))

Multiply by 2

2(2n-7) = 2*1/2 (2a1 + d(n-1))

2(2n-7) = (2a1 + d(n-1))

Distribute

4n -14 = 2a1 +dn -d

The n terms have to be equal

4n = dn

d=4

The constant terms have to be equal

-14 = 2a1 -d

we know d

-14 = 2a1 -4

Add 4 to each side

-14+4 = 2a1-4+4

-10 = 2a1

Divide by 2

-10/2 =2a1/2

-5 =a1

The first term is -5 and the common difference is 4

The term ( you call it tn I call it an)

an = a1+d(n-1)

an = -5+4(n-1)

an = -5 +4n-4

an = -9+4n

User ShockwaveNN
by
4.6k points